Giant uterine cervical polyp: a case report - Guleria, Sara; Thakur, Suman; Pathania, Kushla (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Cervical polyps are benign growths, usually protruding from the surface of the cervical canal. Two out of three women with cervical polyps present asymptomatically. However, symptomatic women usually present with abnormal uterine bleeding, such as heavy menstrual bleeding, intermenstrual bleeding, or postmenopausal bleeding, as well as vaginal discharge. Giant cervical polyps often are misdiagnosed as malignant in view of their appearance, however most of them are benign in nature. They are also confused with uterine prolapse and uterine inversion. Proper evaluation and diagnosis should be provided so as to ensure complete care to the individual and adequate management.